Can HRV Training Make Us Happy: An Experimental Study on University Students - Hamza Kaya Besler (Journal of Educational Issues, 2024)
The purpose of this study is to determine the effect of 8 weeks of HRV (Heart Rate Variability) training on the happiness and coherence levels of university students. According to this purpose, 20 sports management students from the same class volunteered to participate in the study. 10 students were selected randomly as the experimental group while the other 10 were control group. Data was collected with Oxford Happiness Inventory and Inner Balance HeartMath (biofeedback device). 8 weeks of HRV training was applied to the experiment group every night before going to sleep. After 8 weeks, the results showed a significant difference between pretest and post-test results p < 0.05. The experimental group increased their happiness and coherence while the control group decreased. In other words, the experimental group is now happier and more coherent.